Pengaruh Model Pembelajaran Invitation Into Inquiry Terhadap Hasil Belajar Peserta Didik Pada Materi Energi Alternatif Kelas X SMAN 2 Jeneponto - Riki Prayanto; Ali Umar Dani; Andi Ferawati Jafar (Pendidikan Fisika, FKIP, Universitas Nahdlatul Ulama Cirebon, 2026)
This research aims to determine the effect of the Invitation into Inquiry learning model on students' learning outcomes in the topic of alternative energy for grade X students at SMAN 2 Jeneponto. This study used a quasi-experimental design with a non-equivalent pretest-posttest control group design. The sample consisted of two classes selected using cluster random sampling, namely class X.2 as the experimental class and class X.6 as the control class. The experimental class was taught using the Invitation into Inquiry learning model, while the control class used conventional learning methods. Data were collected using multiple-choice tests consisting of 20 items. The results showed that the average posttest score of the experimental class was 72.78, while the control class was 65.28. Hypothesis testing using the Independent Samples t-test showed a significance value of 0.003 < 0.05, indicating a significant difference between the two classes. The N-gain analysis also showed that the improvement in the experimental class was better than the control class. Therefore, the Invitation into Inquiry learning model has a positive effect on students’ learning outcomes in learning physics, especially on alternative energy material.